AB0603 PDGFΑ AS A POTENTIAL BLOOD MARKER IN DSSC. (13th June 2020) - Romanowska-Prochnicka, K.; Wajda, A.; Paradowska-Gorycka, A.; Felis-Giemza, A.; Walczuk, E.; Olesińska, M.
Abstract : Background: PDGF is a potential important factor in the pathogenesis of scleroderma. PDGF is almost undetectable in healthy skin or lung. Immunohistochemical studies have revealed increased presence of PDGF α and PDGF β receptors in scleroderma skin biopsies. Objectives: The aim of this study was to determine the mRNA level of IFNα1, IL-4, TGFβ1, TGFβ2, PDGFα, PDGFβ, TNFα in whole blood in SSc patients in the aspect of clinical Methods: A group of 14 patients (50% were women) with systemic sclerosis based on EULAR / ACR 2013 criteria was included in the study. The modified Rodnan Skin Score (mRSS) was evaluated by same assistant at the beginning of the study and six months later. DLCO, HRCT, echocardiography and NFC were measured. Gene expression was determined using validated TaqMan probes in qPCR. Constitutive mRNA level of selected genes was analyzed using ΔCt method. Comparison between different groups of patients was determined using non-parametric Mann-Whitney U test. Correlation was analyzed using non-parametric Spearman test. Results: The mean age of the patients was 60 ± 15.66. 100% of patients had organ involvement as pulmonary fibrosis. 78% - had active changes -features of ground glass. 64% of patients had mild mRSS-1-10 skin involvement, 36% had moderate to severe skin involvement. In SSc patients TGFβ1 and IFNα1 revealed the highest level of expression in comparison to other analyzed genes. Additionally, very high and significant correlation between TNFα and TGFβ1 (r=0.7 p=0.004) has been noted. High and significant correlation between mRNA PDGFβ and TNFα levels have been observed. We did not reveal significant differences in analyzed genes expression when compare limited and diffuse SSc. Nevertheless, patients with dSSc were characterized by higher level of IFNα1 (almost 2 times) and TGFβ1 . On the border of significance higher PDGFα mRNA level was observed in dSSc patients when compared to lSSc. Average PDGFα expression is higher in SSc patients with Scl70 positive than than in patients without Scl70 (p=0.04). In the aspect of clinical parameters, patients with ESR ≤12 mm/h revealed almost 6 times higher level of IFNα1 (p=0.01) in comparison to the patient with ESR>12mm/h. Patients with mRSS above10 points revealed significantly higher of PDGFα expression in comparison to patients with mRSS ≤10 (p=0.04). In these group of patients CRP and ESR were not different significantly. In the case of patients with active fibrosis (ground glass) in HRCT IFNα1 expression was almost 2.5-times higher than in patients with HRCT non-active. Significantly higher PDGF α has been revealed in patients with active HRCT when compared with patient with non-active HRCT. Nevertheless these two groups did not differ in ESR or OB parameter. SSc patients in active phase of NFC revealed almost 3 times higher level of IFNα1 expression in comparison with the patient in late phase. Conclusion: The mRNA level of PDGFα may be a potential blood marker to predict worse prognosis in scleroderma References: [1]Rheumatology (Oxford). 2008 Oct;47 Suppl 5:v2-4. doi: 10.1093/rheumatology/ken265. Role of PDGF in fibrotic diseases and systemic sclerosis. Trojanowska M1. Acknowledgments: No Disclosure of Interests: None declared